2015
DOI: 10.1136/gutjnl-2015-309647
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer risk factors in patients with serrated polyposis syndrome: a large multicentre study

Abstract: Patients with SPS have an increased risk of CRC, although lower than previously published. Close colonoscopy surveillance in experienced centres show a low risk of developing CRC (1.9% in 5 years). Specific polyp features (SSA/P histology, proximal location and presence of high-grade dysplasia) should be used to guide clinical management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
119
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(137 citation statements)
references
References 46 publications
12
119
0
5
Order By: Relevance
“…At this stage, it is unknown whether geographical differences exist within countries, potentially due to environmental and/or genetic factors, such as diet or smoking habits, justifying the conception of an international study. Second, international studies are needed to enable a proper assessment of the prevalence of individuals with serrated polyposis syndrome (SPS), a syndrome characterised by multiple SPs throughout the colon and accompanied by an increased risk of developing CRC 12 22 23. The aim of this study was to evaluate and compare the detection rate (referred to as rate) of SP subtypes as well as SPS in several European CRC screening cohorts in an attempt to better understand what is reported among Western countries and to enable guidance for detection standards.…”
Section: Introductionmentioning
confidence: 99%
“…At this stage, it is unknown whether geographical differences exist within countries, potentially due to environmental and/or genetic factors, such as diet or smoking habits, justifying the conception of an international study. Second, international studies are needed to enable a proper assessment of the prevalence of individuals with serrated polyposis syndrome (SPS), a syndrome characterised by multiple SPs throughout the colon and accompanied by an increased risk of developing CRC 12 22 23. The aim of this study was to evaluate and compare the detection rate (referred to as rate) of SP subtypes as well as SPS in several European CRC screening cohorts in an attempt to better understand what is reported among Western countries and to enable guidance for detection standards.…”
Section: Introductionmentioning
confidence: 99%
“…A recent multicenter study described a CRC risk of 15%, lower than previously reported, with some specific polyp features associated with a higher risk [61].…”
Section: Serrated Polyposis Syndromementioning
confidence: 79%
“…Thus, Boparai and his colleagues reported that in 35 % of such cases (27 of 77) the SPS was found, and CRC was found in 6.5 % (5 of 77) of those patients [41]. Carballal and colleagues recently reported that the presence of more than two SSA/P, which are more proximal to the splenic fl exure, and one SSA/P in proximal colon with high-grade dysplasia were independent risk factors for CRC (incremental OR=2.95 % CI=1.22-3.24, p=0.006) in patients with SPS [42].…”
Section: Serrated-polyposis Syndrome (Sps)mentioning
confidence: 99%